# Solve each of the following quadratic equations:22x - 3.2(x + 2) + 32 = 0

Given: 22x - 3.2(x + 2) + 32 = 0

(2x)2 - 3.2x.22 + 32 = 0 - - - - (1)

Let 2x = y - - - - - - (2)

substituting for y in (1)

y2 - 12y + 32 = 0

Using the splitting middle term - the middle term of the general equation is divided in two such values that:

Product = a.c

For the given equation a = 1 b = - 12 c = 32

= 1.32 = 32

And either of their sum or difference = b

= - 12

Thus the two terms are - 8 and - 4

Sum = - 8 - 4 = - 12

Product = - 8. - 4 = 32

y2 - 8y - 4y + 32 = 0

y(y - 8) - 4(y - 8) = 0

(y - 8) (y - 4) = 0

(y - 8) = 0 or (y - 4) = 0

y = 8 or y = 4

2x = 8 or 2x = 4

substituting the value of y in (2)

2x = 23 or 2x = 22

x = 2 or x = 3

Hence the roots of equation are 2, 3

Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Related Videos  Get To Know About Quadratic Formula42 mins  Quiz | Knowing the Nature of Roots44 mins  Take a Dip Into Quadratic graphs32 mins  Foundation | Practice Important Questions for Foundation54 mins  Nature of Roots of Quadratic EquationsFREE Class  Getting Familiar with Nature of Roots of Quadratic Equations51 mins  Quadratic Equation: Previous Year NTSE Questions32 mins  Champ Quiz | Quadratic Equation33 mins  Balance the Chemical Equations49 mins  Champ Quiz | Quadratic Equation48 mins
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation view all courses 